Retraction_Designing And Piloting Of Online Interprofessional Education Programme For Medical Students: A-Mixed Method Study - Suryanti Suryanti; Soematri Diantha; Hamzah Hamzah (International Journal of Health Literacy and Science, 2024)
Retraction Notice This article has been formally retracted at the request of the author and with the full consent of the Editor-in-Chief. The retraction has been made due to a confirmed breach of publication ethics associated with the previously published version of the article. After careful consideration and mutual agreement between the author and the editorial team, it was concluded that retraction is necessary to uphold the ethical standards and integrity of the journal.